Oral exploration and food selectivity: A case-control study conducted in a multidisciplinary outpatient setting - Bellaïche, Marc; Leblanc, Véronique; Viala, Jérôme; Jung, Camille (Frontiers in Pediatrics, 2023)
Background: Pediatric feeding disorders (PFDs) are common, and their great phenotypic variability reflects the breadth of the associated nosological profiles. PFDs should be assessed and managed by multidisciplinary teams. Our study aimed to describe clinical signs of feeding difficulties in a group of PFD patients assessed by such a team, and to compare them with children in a control group. Methods: In this case-control study, case group patients 1 to 6 years old were consecutively recruited through the multidisciplinary unit for the treatment of pediatric feeding difficulties based at Robert Debré Teaching Hospital in Paris, France. Children with an encephalopathy, severe neurometabolic disorder, or genetic syndrome (suspected or confirmed) were excluded. Members of the control group, consisting of children with no feeding difficulties (i.e., Montreal Children’s Hospital Feeding Scale scores below 60) or severe chronic diseases, were recruited from a day care center and 2 kindergartens. Data from medical histories and clinical examination related to mealtime practices, oral motor skills, neurodevelopment, sensory processing, and any functional gastrointestinal disorders (FGIDs) were recorded and compared between groups. Results: In all, 244 PFD cases were compared with 109 controls (mean ages: cases, 3.42 [± 1.47]; controls, 3.32 [± 1.17]; P = 0.55). Use of distractions during meals was much more among PFD children (cases, 77.46%; controls, 5.5%; P < 0.001), as was conflict during meals. While the groups did not differ in their members’ hand-mouth coordination or ability to grab objects, cases began exploring their environments later; mouthing, especially, was less common in the case group (cases, n = 80 [32.92%]; controls, n = 102 [94.44%]; P < 0.001). FGIDs and signs of visual, olfactory, tactile, and oral hypersensitivity were significantly more frequent among cases. Conclusion: Initial clinical assessments showed that, in the children with PFDs, normal stages of environmental exploration were altered, and that this was often associated with signs of sensory hypersensitivity and digestive discomfort.